Clinical profile, management and early outcome of gall bladder cancer - Kumar, S; Kafle, P; Maharjan, N; Patowary, BN; Belbase, N; Shrestha, SJ; Agrawal, S (Journal of College of Medical Sciences-Nepal, 2014)
Objective To evaluate the clinical profile, management and early outcome of patients with gallbladder cancer. Methods This is a single institution based retrospective study of patients with gallbladder cancer who presented at College of Medical Sciences and Teaching Hospital, Bharatpur, Chitwan, Nepal. Patients presenting during one year period from August 2012 to July 2013 were reviewed. Results Twelve cases of Gall Bladder Cancer were reviewed in this series. Out of 12 patients, 9 were females (75%) and 3 were males (25%), showing female preponderance. Most of the patients (75%) were in age group of 51-70 years. Only one patient (8%) was below 50 years of age. Main symptom was pain associated with anorexia, nausea & vomiting. Major signs were palpable mass, hepatomegaly and jaundice. All the cases had association with gall bladder stone. Of the total population, 50%(n=6) underwent extended cholecystectomy and rest of 6 cases were inoperable. Histopathological reports of all the operated cases were adenocarcinoma. Conclusion Prevalence of gall bladder cancer is higher in females in our series. Most of the patients were in fifth to seventh decade of life. Non specific symptoms like abdominal pain nausea and vomiting were the predominant symptoms. Only 50% of the cases were operable. So we have to do early screening by USG abdomen and CT scan to diagnose the disease earlier. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-3, 12-16